Nano-enabled strategies for targeted immunotherapy in gastrointestinal cancers - Chen, Chaofan; Li, Jinlei; Hua, Xiaokun; Deng, Tingting; Zhang, Zhiyun (Frontiers in Immunology, 2025)
Gastrointestinal (GI) cancers remain a leading cause of global cancer morbidity and mortality, demanding novel therapeutic strategies that overcome existing limitations. Nanomedicine has recently emerged as a transformative approach, offering the potential to significantly enhance immunotherapy outcomes through precision targeting and modulation of tumour immune microenvironments. This review discusses the principal categories of precision-engineered nanoparticles—including lipid-based carriers, polymeric systems, protein-derived formulations, and metallic-hybrid composites—emphasising their capacity for targeted immune modulation and improved pharmacokinetic profiles. These nanoparticle platforms strategically intervene across multiple stages of the cancer-immunity cycle, facilitating antigen presentation, T-cell activation, and cytotoxic lymphocyte infiltration, and augmenting immune checkpoint blockade efficacy. Clinically approved nanoformulations such as Abraxane, Doxil, Onivyde, and emerging mRNA-based nanovaccines highlight promising translational outcomes in GI malignancies, demonstrating improved therapeutic indices and reduced systemic toxicity. Nonetheless, clinical implementation remains challenged by nanoparticle complexity, heterogeneous tumour biology, clearance mechanisms, and toxicity concerns. Future success will depend on integrated strategies combining advanced nanoparticle engineering, precise administration routes, rigorous translational validation, and rational therapeutic combinations to realise the full potential of nanomedicine-based immunotherapies in gastrointestinal oncology.